An investigation of the effect of dynamic and static loading to geosynthetic reinforced pavements overlying a soft subgrade - Kiptoo, Dennis Kipngetich (Department of Civil Engineering, 2016)
Construction of roads over soft soils can lead to design and construction related problems linked to the soil's compressibility characteristics and low strength. Failure, in terms of bearing capacity can occur when pavements are constructed over such soft soils. When road pavements, which are constructed over soft soils, are subjected to cyclic traffic loading (dynamic in nature), rapid deterioration of the base layer material and progressive permanent deformation of the surface will occur. This not only reduces the serviceability of the pavement structure but also its design life. In this study, reinforcement geosynthetics (geogrids and geotextiles) were used as reinforcement inclusions within a granular base overlying a soft subgrade of California Bearing Ratio (CBR) less than 2% in a 1.0 m3 steel test box. Firstly, a geotextile/geogrid was placed at the interface between the base layer and subgrade. Thereafter, a combination of the geotextile at the interface (of the base and subgrade) and geogrid within the base layer. Bench scale plate load tests (static and cyclic) were conducted on a 305 mm diameter circular steel plate on the two layer system using a Universal Compression Machine. Static loading was applied at a rate of 1.2 mm/min. Dynamic sinusoidal load wave was applied with a 4 kN seating load that was linearly increased with an incremental load of 4 kN for every 8 cycles at a frequency of 0.2 Hz on a 305 mm circular plate. For both tests, settlement failure of the composite system was considered at a deformation of 75 mm as defined for unpaved roads. The results obtained from the pavement model showed that there was a significant improvement in bearing capacity and reduction in settlement accruing from geosynthetic inclusion as shown by the Bearing Capacity Ratio (BCR) of 1.21, 1.29 and 1.63 for geogrid, geotextile and geogrid-geotextile combinations respectively. Additionally, a Settlement Reduction Factor (SRF) of 18% for geogrid, 23% for geotextile and 31% for the geogrid-geotextile combination resulted. There was also an improvement in extended pavement life as depicted by the Traffic Benefit Ratio (TBR) greater than 1 for all reinforced base layers. An improved performance was realised with the double combination of geotextile at the interface, geogrid at the base.